1987
DOI: 10.1111/j.1365-4362.1987.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Systemic Sclerosis Occurring in Patients Exposed to Chemicals

Abstract: Eight patients with systemic sclerosis previously exposed to organic chemical agents were investigated. Laboratory and clinical data of these patients were evaluated. The interval between the beginning of exposition and symptoms was 6.1 +/- 4.9 years. Considering the laboratory findings, a slight decrease in OKT4 positive T cell number was found. The antinucleolar and fine speckled antinuclear antibody pattern was found simultaneously in five cases. The possible role of chemical agents in the development of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Anti-Scl-70 positive scleroderma cases seem to be more susceptible to the effects of solvents [19,20]. Previous studies, apart from that by Yamakage and Ishikawa [21] and our previous East-Hungarian publications [22,23], have described predominantly male workers [1,3] Only a few controlled studies are available about the provoking effect of solvents in scleroderma. In a population-based case reference study, Bovenzi et al demonstrated a significant association between occupational exposure and SSc with an odds ratio of 9.28 [7].…”
Section: Introductionmentioning
confidence: 98%
“…Anti-Scl-70 positive scleroderma cases seem to be more susceptible to the effects of solvents [19,20]. Previous studies, apart from that by Yamakage and Ishikawa [21] and our previous East-Hungarian publications [22,23], have described predominantly male workers [1,3] Only a few controlled studies are available about the provoking effect of solvents in scleroderma. In a population-based case reference study, Bovenzi et al demonstrated a significant association between occupational exposure and SSc with an odds ratio of 9.28 [7].…”
Section: Introductionmentioning
confidence: 98%
“…Scleroderma has been associated with exposure to vinyl chloride, silica, contaminated rape seed oil, l-triptophan, uranium, quartz, and some other agents. 2 Both of our patients were housewives, but because the places they lived in were quite different, it was difficult to determine the influences of environmental factors. Immunogenetic associations were studied first in families, and later by an analysis of the prevalence of MHC alleles associated with systemic sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for the influence of a diverse range of environmental agents from silica to cocaine. 2 On the other hand, there is also thought to be an association with human leukocyte antigen (HLA) class I and II alleles, specifically DP, DQ, and DR, and the major histocompatibility complex (MHC). Molecular genetic research has found susceptibility alleles and discriminated between DP, DQ, and DR. As yet, there is no clear pattern of association between specific MHC antigens or alleles and systemic sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…This newly recognized case indicates that the development of morphea can also be connected with exposure to solvents. Among the cases exposed to solvents, trichloroethylene was described in only a few cases with SSc [2,4,7,12] including in 1 Hungarian patient [6], It is noteworthy that among the other solvents, trichloroethylene and tetrachloroethylene were found to be the provoking agents as in this particular case.…”
Section: Discussionmentioning
confidence: 99%